Adverse Effects of Medications for ADHD: Priapism with Medication for ADHD - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Auburn University, Huntsville, AL, and other centers, reviewed reports in the literature (1966-May 15, 2014) of priapism associated with methylphenidate (MPH), amphetamines, and atomoxetine used in treatment of ADHD.